PENGARUH DAYA TARIK WISATA DAN FASILITAS WISATA DALAM KEPUTUSAN BERKUNJUNG KE TAMAN SAFARI INDONESIA KECAMATAN CISARUA KABUPATEN BOGOR - Paulina, Ruth; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
ABSTRACT This study examines the impact of tourism attractions and facilities on the decision to visit Taman Safari Indonesia, Cisarua, Bogor. Tourism attractions include aspects that make a destination attractive, while tourism facilities include infrastructure and services that enhance visitor comfort. Taman Safari Indonesia offers the experience of interacting directly with wildlife, which adds educational and recreational value. A survey was conducted on visitors to Taman Safari Indonesia to collect data. Analysis using SPSS shows that Tourist Attraction (X1) with a coefficient of 0.235 (t count 2.276 > t table 1.987, p-value 0.025 < 0.05) and Tourist Facility (X2) with a coefficient of 0.540 (t count 7.116 > t table 1.987, p-value 0.000 < 0.05) have a significant positive influence on Visiting Decision (Y). The simultaneous F test (F count 210.779 > F table 3.087, p-value 0.000) and R Square 0.813 indicate a strong model, explaining 81.3% of the variation in Visiting Decisions. The results showed that attractions and tourist facilities greatly influenced the decision to visit Taman Safari Indonesia. Keywords: Tourist Attractions, Tourist Facilities, Visiting Decisions, Safari Park Indonesia